High temperature oxidation behaviour of AISI 321 stainless steel with an ultrafine-grained surface at 800 °C in Ar–20 vol.% O2 - Pour-Ali, Sadegh; Weiser, Martin; Nguyen, Nhat Truong; Kiani-Rashid, Ali Reza; Babakhani, Abolfazl; Virtanen, Sannakaisa (Corrosion Science, 2019)
Oxidation behaviour of surface nanocrystallized 321 austenitic stainless steel (SN–321ASS) and its conventional polycrystalline counterpart (CP–321ASS) in Ar + 20% O2 at 800 °C is comparatively investigated. Severe breakaway oxidation sets in for the CP–321ASS after 100 h, while the SN–321ASS shows a higher oxidation resistance. Surface nanocrystallization increases the diffusion and flux of Cr towards the oxidation front, and can consequently promote the kinetics of early oxidation and accelerate the formation of a thicker Cr-rich inner oxide layer, which aids in prohibiting the enhanced formation of Fe-rich oxides.
CRIS-Team Scopus Importer:2019-10-29
Keywords: A. Stainless steel; B. TEM; B. XRD; C. Oxidation